2016
DOI: 10.1080/21505594.2016.1270494
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies toStaphylococcus aureuscapsular polysaccharides 5 and 8 perform similarlyin vitrobut are functionally distinctin vivo

Abstract: The capsular polysaccharide (CP) produced by Staphylococcus aureus is a virulence factor that allows the organism to evade uptake and killing by host neutrophils. Polyclonal antibodies to the serotype 5 (CP5) and type 8 (CP8) capsular polysaccharides are opsonic and protect mice against experimental bacteremia provoked by encapsulated staphylococci. Thus, passive immunotherapy using CP antibodies has been considered for the prevention or treatment of invasive antibioticresistant S. aureus infections. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 81 publications
(90 reference statements)
0
16
0
Order By: Relevance
“…We reported that S. aureus CP was shed from broth-grown S. aureus cells 59 , and it is feasible that EVs could serve as a vehicle to liberate CP from the cell envelope. The Streptococcus pneumoniae capsule was reported to hinder EV release in this pathogen 7 , whereas no effect was observed on EV yield in strains with or without the hyaluronic capsule of Streptococcus pyogenes 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that S. aureus CP was shed from broth-grown S. aureus cells 59 , and it is feasible that EVs could serve as a vehicle to liberate CP from the cell envelope. The Streptococcus pneumoniae capsule was reported to hinder EV release in this pathogen 7 , whereas no effect was observed on EV yield in strains with or without the hyaluronic capsule of Streptococcus pyogenes 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The membranes were immersed in PBST + 5% skim milk for 2 h before blocking the staphylococcal IgG binding proteins (Spa and Sbi) by overnight incubation at 4 °C with an irrelevant human IgG1 monoclonal antibody (10 µg ml −1 ) in PBST + 1% skim milk. The membrane was washed with PBST and incubated overnight at 4 °C with sera (diluted 1:1000 in PBST + 1% skim milk) pooled from mice immunized with EVs (see below) or murine mAbs 59 to CP5 (4C2; 1.2 µg ml −1 ) or CP8 (5A6; 1.2 µg ml −1 ). After washes with PBST, the membrane was incubated with alkaline phosphatase (AP)-conjugated goat anti-mouse antibody (1:15,000; Sigma; Cat.…”
Section: Methodsmentioning
confidence: 99%
“…In the study, USA300 LAC and MW2 strains were used to show that MgrA has a positive effect on attachment to endothelial cells, which is in contrast to our results. USA300 strains are known to produce no capsule because of multiple mutations in the cap locus (45), whereas MW2 produces only a scant amount of capsule due to a frameshift mutation in one of the cap genes (46). As such, regulation of capsule by MgrA would not play a role in cell attachment in USA300 LAC and MW2, which may explain, in part, the difference between their and our studies.…”
Section: Discussionmentioning
confidence: 55%
“…S. aureus CPs were associated with or packaged within EVs isolated from S. aureus strain Newman and MN8 in our study. We reported that S. aureus CP was shed from broth-grown S. aureus cells 78 , and it is feasible that EVs could serve as a vehicle to liberate CP from the cell envelope. The S. pneumonia capsule was reported to hinder EV release in this pathogen 7 , whereas no effect was observed on EV yield in strains with or without the hyaluronic capsule of S. pyogenes 8 .…”
Section: Discussionmentioning
confidence: 99%
“…To block the staphylococcal IgG binding proteins Spa and Sbi, the membranes were blocked with PBST + 5% skim milk and incubated overnight at 4°C with an irrelevant human IgG1 monoclonal antibody (10 μg/ml) in PBST + 1% skim milk. The membrane was washed with PBST and incubated overnight at 4°C with sera (diluted 1:1000 in PBST + 1% skim milk) pooled from mice immunized with EVs (see below) or murine mAbs 78 to CP5 (4C2; 1.2 μg/ml) or CP8 (5A6; 1.2 μg/ml). After washes with PBST, the membrane was incubated with alkaline phosphatase (AP)-conjugated goat anti-mouse antibody (1:15000 dilution in PBST + 1% skim milk) at RT for 2 h. The membrane was washed with PBST and developed with AP membrane substrate (KPL).…”
Section: Methodsmentioning
confidence: 99%